Perfil imunoistoquímico dos linfomas difusos de grandes células B caninos utilizando-se o método de microarranjo de tecido (TMA) - Silva, Maria Claudia Lopes da [UNESP] (2015)
Non Hodgkin lymphomas (LNHs) are the most common hematopoietic tumors of dogs, among which Diffuse Large B Cell Lymphoma (DLBCL) is the most frequent subtype. DLBCLs are tumors composed of lymphoid B cell with a diffuse growth pattern and may present at least five variants. The present work intended to delineate the immunohistochemical profile of canine DLBCL, classify them according to the criteria proposed by WHO (2008); veterinary WHO (2002) and Updated Kiel Classification and also perform the evaluation of the used antibodies on tissue microarray (TMA) method in comparison to conventional histological sections. The immunohistochemical expression of pan B markers (anti CD79a, anti CD20 and PAX-5) was assessed; as well as the determination of proliferation index (Ki-67) and apoptosis (caspase 3) and also the expression of the mutant p53. There were 24 monomorphic centroblastic lymphomas, 4 imunoblastic B and 1 polimorphic centroblastic according to Kiel. That profile is 25 Diffuse Large B Cell Lymphoma/ DLBCL, NOS centroblastic variant and 4 Large Cell Imunoblastic/ DLBCL, NOS imunoblastic variant according to WHO 2002 and 2008 respectively. Immunolabeling was seen in 100%, 75.8% and 58.6% of the cases for CD79a, CD20 and PAX-5 respectively. The immunolabeling median percentage of Ki67 was 45.9% and for caspase-3 it was 10%. The expression of mutant p53 was observed in 16 tumors (55.1%). The analysis of those markers using TMA resulted in identical imunophenotype and significantly similar medians of caspase-3, Ki67 e p53 when compared to conventional sections. In conclusion there was no statistical difference among the histological subtypes regarding proliferation and apoptotic indexes and p53 expression in our samples. Also, TMA is an adequate technique for evaluating imunophenotype, proliferation and apoptotic indexes as well as presence of mutant p53